EDUCATION LEVEL, INFRASTRUCTURE, AND CAPACITY BUILDING ON THE PERFORMANCE OF AGRICULTURAL EXTENDERS AT THE FOOD SECURITY AND AGRICULTURAL SERVICES - Nia Kurniasari; Ellin Herlina (Journal Of Resource Management, Economics And Business, 2022)
Purpose: To determine the effect of education level, infrastructure and capacity building on the performance of agricultural extension workers at the Food and Agriculture Security Service. Research Methodology: This type of research is a causal associative research using a quantitative approach with the survey method. The population in this study were 256 agricultural extension workers from the Department of Food Security and Agriculture. The technique used in sampling in this study is by proportionate stratified random sampling using the Slovin formula as many as 72 people. Results: The magnitude of the influence of the level of education on the performance of agricultural instructors is 57.7%, while the remaining 42.3% is influenced by other factors. The magnitude of the influence of infrastructure on the performance of agricultural instructors is 79.4%, the remaining 20.6% is influenced by other factors. The magnitude of the effect of Capacity Building on the Performance of Agricultural Extension Officers is only 73.7% while the remaining 26.3% is influenced by other factors. The magnitude of the positive influence of the level of education, infrastructure, capacity building on the performance of agricultural instructors is 83.4% while the remaining 16.6% is influenced by other factors. Limitations: The variables used are limited to Organizational culture, Organizational Commitment, Work Discipline, Employee Performance. Contribution: The development of science, especially in the field of extension and becomes the starting point for more in-depth research on the performance of agricultural extension workers. It is hoped that this can be taken into consideration for the institutional extension workers and can assist in evaluating the performance of agricultural extension workers. The results of this study can be used as reference material for further research in more depth.